2017
DOI: 10.18178/ijiet.2017.7.3.871
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Student Motivation, Self-regulation, and Engagement in Flipped Classroom to Decrease Boredom

Abstract: Abstract-The interplay teacher regulation and student self-regulation of learning is an important topic in contemporary theories of teaching and learning. The pervasiveness of the boredom experienced by many students, along with its deleterious effects, clearly implies that educators, and teachers responsible for the design of academic settings should pay more attention to this emotion. With regard to the prevention or reduction of boredom, the present findings suggest that specific measures could focus on inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 15 publications
(16 reference statements)
0
18
0
Order By: Relevance
“…Yang (2017) found that finding or making proper videos was the main concern for teachers. For a successful implementation of the flipped classroom, it is also important to present quality online learning materials to the students in terms of video and audio quality (Akçayır & Akçayır, 2018;La Marca & Longo, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yang (2017) found that finding or making proper videos was the main concern for teachers. For a successful implementation of the flipped classroom, it is also important to present quality online learning materials to the students in terms of video and audio quality (Akçayır & Akçayır, 2018;La Marca & Longo, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This allows students the opportunity to participate in various active learning activities such as question-answer, discussion, group work, and problem-solving during course time (Findlay-Thompson & Mombourquette, 2014;Şengel, 2016). The course hours are mostly devoted to interactive activities to enable students to have a clear understanding and reinforcement of the concepts they view in pre-recorded videos (La Marca & Longo, 2017). Students can also learn the course content at their own pace by pausing, rewinding, and fast-forwarding these videos without any time and space limitations (Chuang, Weng, & Chen, 2018;Moos & Bonde, 2016;Sun, Wu, & Lee, 2017).…”
Section: What Is the Flipped Classroom?mentioning
confidence: 99%
See 1 more Smart Citation
“…Monitoring students' interest and motivation with the course content can be helpful as instructors work to facilitate learning in the classroom. To some students, the material taught is sometimes seen as meaningless and not valuable, thus contributing to a student's boredom (4). If instructors begin to notice issues in their classroom with students appearing to be uninterested, zoning out, or having a lack of participation, they can amend their approaches to help fuel student learning.…”
Section: Introductionmentioning
confidence: 99%
“…The students in 21st century STEM learning environment need to enhance their creativity and critical thinking to make sure they can fully concentrate during the learning session in a perfect condition. The learner-centered approach is able to get rid of boredom; hence, accelerate the learning process (Marca & Longo, 2017;Hanipah Hussin, 2004). In a critical review reported by Jayarajah, Saat, and Rauf (2014), the researchers stated that little research has been documented to determine the effects of the integrated approaches among the STEM subjects on the students' achievement and the infusion between STEM disciplines.…”
Section: Introductionmentioning
confidence: 99%